Motivational Profiles and Career Decision Making of High School Students. Issue 3 (September 2017) - Paixão, Olímpio; Gamboa, Vítor
Abstract : Based on self‐determination theory, this study sought to identify distinct motivational profiles in a sample of high school students ( N = 396, mean age = 17.02 years) using a person‐centered approach. Three motivational clusters of students emerged: self‐determined students, non‐self‐determined students, and externally regulated students. Differences between and among these profiles across career exploration and career indecision levels were analyzed. Overall, self‐determination theory appears to offer a conceptual framework for organizing career interventions. The fact that motivational profiles can distinguish students among career exploration and career indecision levels leads the authors to reaffirm the importance of differential career intervention practices. Future research should examine the stability of motivational profiles, their predictive power over career exploration and career decision making, and the differences between highly motivated students regarding the career decision‐making process.